Chromatographic Identification of Some Flavonoids of Matricaria Chamomilla Growing in Iraq - Moayed Mohamed (College of Education for Pure Sciences, 2010)
ABSTRACT Ethanolic extract of the flower-head of matricaria chamomilla which growing in Iraq showed the presence at last of two new flavonoids quercetin (III) and isorhamnetin (IV), which gave a bright yellow colour during TLC separating under U.V light. These compounds were investigated on the basis of the comparison of their Rf-values in tables and using quercetin as authentic sample for comparison.